GASZACK: DESIGN AND CONSTRUCTION OF A GAS LEAK DETECTION DEVICE BASED ON SENSORS AND BUZZERS AS AN EARLY WARNING SYSTEM - Ahmad Daffa Athallah; Rafif Raihan Hafizh; Abdurrahman Yusuf Adya (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2026)
LPG gas leakage is a serious hazard that frequently triggers explosions and fires in residential areas. GASZACK was developed as an appropriate technology-based early warning system utilizing an MQ-2 sensor and an Arduino Uno microcontroller. The device is designed to detect hazardous gas concentrations and instantly activate a buzzer alarm as a warning mechanism. The testing results demonstrated that the system achieved a response time of less than 5 seconds with sufficient accuracy for household-scale applications. This innovation offers an economical and easily replicable self-protection solution for communities to minimize the impact of accidents caused by gas leakage.